Innovative recyclable pouch in pouch packaging with biodegradable and polyolefin-based films for oxygen and moisture sensitive products - Umm E. Salma; Muhammad Abdul Haq; Syed Arsalan Ali; Syed Muhammad Ghufran Saeed; Shagufta Ishtiyaque; Lubna Mobin; Manal F. Elkhadragy; Basim M. Alohali; Hany M. Yehia (International Journal of Food Properties)
The present study proposes a composite packaging system comprising two pouches: an outer layer made of moisture-resistant biaxially oriented polypropylene (BOPP) film and an inner layer using oxygen-barrier biodegradable polymer films, such as starch or polyvinyl alcohol (PVA). The biodegradable inner pouch enhances sustainability by reducing plastic waste, while the single-polymer composition of the outer pouch facilitates recyclability. The formulation of the inner biodegradable pouches was refined using starch/PVA, with glycerol as a plasticizer and tannic acid (TA) as a crosslinking agent. Results revealed that glycerol and TA concentrations significantly affected the film properties, and optimal ranges were identified to balance flexibility and barrier performance. Among the two biodegradable options, PVA films demonstrated superior packaging characteristics. A pouch-in-pouch system was developed, characterized, and tested for preserving red chili powder and deshelled peanuts stored under daylight at 40°C for seven weeks. Of the ten packaging configurations evaluated, the PVA-TA/BOPP combination showed exceptional preservation performance, with the lowest oxygen transmission rate and the ability to maintain 95% of chili powder pungency and American Spice Trade Association (ASTA) color value. Similarly, favorable moisture content and peroxide values were observed in deshelled peanuts. This research highlights the potential of biodegradable packaging systems, optimized through material selection and additive incorporation, to enhance food preservation in packaging applications.